2006
DOI: 10.1149/1.2164768
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization Behavior and Physical Properties of Sb-Excess Ge[sub 2]Sb[sub 2+x]Te[sub 5] Thin Films for Phase Change Memory (PCM) Devices

Abstract: The crystallization behavior of antimony͑Sb͒-excess Ge 2 Sb 2+x Te 5 was examined. Sb-excess GST showed crystallization ͑T C ͒ and melting ͑T M ͒ temperatures of 205 and 550°C, respectively, slightly higher T C and lower T M values than stoichiometric Ge 2 Sb 2 Te 5 compounds. It also showed a substantially different crystallization behavior compared to the stoichiometric Ge 2 Sb 2 Te 5 composition. The resulting Sb-excess GeSbTe thin film showed a grain growth dominated crystallization behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 3 publications
0
26
0
Order By: Relevance
“…The time required for programming was measured for reset (t reset ) and set (t set ) operations as a function of applied pulse width 56) has a slightly lower crystallization activation energy than GST(15/47/38), suggesting that crystallization of GST(22/22/56) occurs somewhat more readily than that of GST(15/47/38). 3 Consequently, the GST(22/22/56) device is expected to have faster setting performance. To resolve this discrepancy a more detailed microstructure analysis was performed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The time required for programming was measured for reset (t reset ) and set (t set ) operations as a function of applied pulse width 56) has a slightly lower crystallization activation energy than GST(15/47/38), suggesting that crystallization of GST(22/22/56) occurs somewhat more readily than that of GST(15/47/38). 3 Consequently, the GST(22/22/56) device is expected to have faster setting performance. To resolve this discrepancy a more detailed microstructure analysis was performed.…”
Section: Resultsmentioning
confidence: 99%
“…The method of sample preparation has been previously described in detail. 3 The GST(22/22/56) and GST (15/47/38) films were freshly deposited by means of RF magnetron sputtering at room temperature. The prepared specimens were then moved into the TEM vacuum chamber.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects give rise to the formation of a non-stoichiometric GST compound with different crystallization and melting temperature. An altered GST compound such as the Ge 15 Sb 47 Te 38 shown a lower crystallization temperature of about 70°C and a higher melting temperature of about 40°C, with respect to Ge 2 Sb 2 Te 5 [4,9]. Furthermore the sheet resistance in crystalline state is about 100 times lower than stoichiometric GST.…”
Section: Discussionmentioning
confidence: 97%
“…In deep, recent material studies [8] on cell structures very similar to that exploited in this work, shown that the proportion of Te (both in crystalline and amorphous phase) vary inversely with the temperature gradient during the cell programming, with consequent effects on the successive erase operations. Moreover, in [9] has been reported that the Te deficiency and the accompanying Sb enrichment are triggered by segregation reactions into Ti composing the heater element, arising the presence of intermetallic compounds. Measurements performed on single cell test structures proven that after multiple programming cycles, cross-sectional transmission electron microscopy and energy dispersive analysis show that electromigration as well as incongruent melting causes phase separation by mass movement by which the peak position of Sb and Ge lies shifted toward the cathode of the structure and that of Te toward the anode structure [10].…”
Section: Discussionmentioning
confidence: 99%